Analisis peran guru dalam meningkatkan keterampilan berpikir fluency pada peserta didik sekolah dasar - Kanthil Esti Winahyu; Siti Istiyati; Hadiyah Hadiyah (Didaktika Dwija Indria, 2021)
The purpose of this study was to describe the results of an elementary teacher's role analysis in the Hasanuddin Cluster 2020/2021 force-enhancing skills of fluency elementary school students. The type of this study was a qualitative study carried out in November 2020 with case study approaches. The research subjects were 4th, 5th, and 6th class teachers and 4th, 5th, and 6th grade elementary students on Hasanuddin Clusters. The technique used in sample retrieval was an impressive sampling technique. The data-collection techniques used were observation, interview, questioner, and documentation. The validity of the data used was engineering triangulation. The data analysis techniques used were Miles and Huberman data analysis techniques composed of data collection, data reduction, data presentation and deduction. The study had the results of 4th, 5th, and 6th teachers of Hasanuddin's fourth generation could act as informators, initiators, directors and motivators to improve student’s ability to produce and improve ideas, improve education and momentum.